SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT TANAMAN BAWANG MERAH DENGAN METODE CASE BASED REASONING BERBASIS WEB (Studi Kasus : Kebun Bawang Merah di Desa Cidokom) - Galuh Saputri; Rizqa Rahmawati (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The expert system for diagnosing shallot disease is a computer application designed to assist farmers or agricultural experts in diagnosing diseases that attack shallot plants. This system uses the knowledge and experience of experts in the agricultural sector to provide recommendations for proper disease diagnoses and control solutions. The Case Based Reasoning (CBR) method is a method that has the concept of comparing old cases with new cases in order to produce a more accurate diagnosis in cases that occur. The Nearest Neighbor Similarity (NNS) method is a method of calculating the level of similarity between symptoms to one another so that these two methods will produce collaboration that is able to answer problems that exist in the field.